Promoting Religious Moderation through Multicultural Problem-Based Learning: A Study in Elementary Education - Rudianto, Apip; Maftuh, Bunyamin; Agustin, Mubiar; Syaodih, Ernawulan; Salahudin, Anas (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractIndonesia is a country with immense diversity in religion, culture, and ethnicity. This diversity serves as both a wealth and a challenge in building a harmonious and tolerant society. In social reality, unmanaged differences could lead to prejudice, discrimination, and even intergroup conflict. The objectives of this study were to examine the effectiveness of multicultural problem-based learning, to identify teachers' perceptions, and to assess the contribution of this approach in fostering a tolerant, inclusive, and diversity-appreciating character in line with religious moderation values in primary education. The research employed a mixed-methods approach, presenting qualitative data gathered from interviews and quantitative data collected through a Google Form questionnaire distributed to elementary school (SD) and Islamic elementary school (MI) teachers in Kuningan Regency, West Java, Indonesia. The findings demonstrated that multicultural problem-based learning was viewed very positively by SD and MI teachers, as it effectively familiarised students with the values of diversity, tolerance, and inclusiveness while strengthening their character and 21st-century skills. This approach was deliberately strategic in promoting religious moderation, attitudes, and building a peaceful and inclusive educational ecosystem.Keywords: multicultural education, problem-based learning, religious moderation attitude.AbstrakIndonesia adalah negara dengan keragaman agama, budaya, dan suku yang sangat besar. Keragaman ini berfungsi sebagai kekayaan sekaligus tantangan dalam membangun masyarakat yang harmonis dan toleran. Dalam realitas sosial, perbedaan yang tidak terkelola dapat menyebabkan prasangka, diskriminasi, dan bahkan konflik antarkelompok. Tujuan penelitian ini adalah untuk mengkaji efektivitas pembelajaran berbasis masalah multikultural, mengidentifikasi persepsi guru, dan mengkaji kontribusi pendekatan ini dalam menumbuhkan karakter yang toleran, inklusif, dan menghargai keragaman yang sejalan dengan nilai-nilai moderasi beragama di pendidikan dasar. Penelitian ini menggunakan pendekatan metode campuran, menyajikan data kualitatif yang dikumpulkan dari wawancara dan data kuantitatif yang dikumpulkan melalui kuesioner Google Form yang disebarkan kepada guru sekolah dasar (SD) dan Madrasah Ibtidaiyah (MI) di Kabupaten Kuningan, Jawa Barat, Indonesia. Temuan penelitian menunjukkan bahwa pembelajaran berbasis masalah multikultural dipandang sangat positif oleh guru SD dan MI, karena secara efektif membiasakan siswa dengan nilai-nilai keragaman, toleransi, dan inklusivitas sekaligus memperkuat karakter dan keterampilan abad ke-21 siswa. Pendekatan ini sengaja dibuat strategis dalam mempromosikan moderasi beragama, sikap, dan membangun ekosistem pendidikan yang damai dan inklusif.Kata kunci: pendidikan multikultural, pembelajaran berbasis masalah, sikap moderasi beragama.